MODEL PENGENTASAN KEMISKINAN TERINTEGRASI DI KOTA YOGYAKARTA - Bellarminus, Gunardo Robertus (Geomedia Majalah Ilmiah dan Informasi Kegeografian, 2018)
This research aim to find model reduction poorness of integrated in Yogyakarta testing having taken steps in three subdistrict that is Kricak, Tegalpanggung and Sorosutan . Research method by using research model and expansion with antecedent study stages; steps, expansion prototype , field test and semination product result of expansion. Antecedent study by doing in-depth interview and observation to poor family , and public figures and studies documents ( former research, institute report) which with reference to reduction poorness. Result of firststep study in the form of information of aspiration of poor family, the Government plan and Non Government Organization and research conclusion before all, utilized isn't it to compile expansion of model prototype reduction poorness. Step of hereinafter test prototype model reduction poorness of three sub-district Kricak, Tegalpanggung and Sorosutan to obtain empiric evidence about elegibility of execution process from model limitedly, either its(the subject and also aspects). Result of his its would in semination to some other sub-districts. Its the target is find enableness model of public in the form of expansion of model reduction poorness integrated, mean from various aspects ( economics, social, education, health, culture) and various element considered and its the execution is really can lessen number of poor families Kata Kunci: kemiskinan, Yogyakarta, integrasi